Study on Evolution Mechanism of Insurance Market Risk under Information Technology Revolution - Ma, Jianxin (Advances in Social Sciences Research Journal, 2018)
Advances in information technologies has changed the way humans are interconnected and brought deep revolution in society, economics and culture. Similarly, the change to the insurance industry is non-negligible. The thesis aims to understand the direction of transformation of the industry and the evolution mechanism of internal systemic risks. Looking at the systemic risk of the insurance market from the perspective of a complex network, it is can be discovered that the occurrence of risk should not only focus on individual risk behaviors or risk factors, but more importantly, it should examine the non-linear relationships among individuals within the network, and in particular the emergent risk evolution mechanism leading to risks. In this research, the author builds a market network simulation model based on the evolution mechanism of the complex network of the insurance market in the analysis of the previous section. The author continues to explore the further evolutionary trend of the insurance market when the sales business method changes based on new technology. The model can be used as a case of the analysis of the evolution mechanism of the insurance market risk.